1999
DOI: 10.1128/iai.67.2.554-561.1999
|View full text |Cite
|
Sign up to set email alerts
|

Consequences of Reduction of Klebsiella pneumoniae Capsule Expression on Interactions of This Bacterium with Epithelial Cells

Abstract: Most Klebsiella pneumoniae clinical isolates are fully encapsulated and adhere in vitro to intestinal cell lines with an aggregative pattern. In this study, the influence of the capsule on interactions with epithelial cells was investigated by creating an isogenic mutant defective in the synthesis of the capsule. Determination of the uronic acid content of bacterial extracts confirmed that the mutant did not produce capsular polysaccharides whereas, with the wild-type strain, the level of encapsulation was gro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
45
0

Year Published

1999
1999
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(50 citation statements)
references
References 37 publications
5
45
0
Order By: Relevance
“…Expression of capsule in some way interferes with one of the ¢nal stages of ¢mbrial assembly. A similar inverse relationship has recently been described for CF29K adhesin of K. pneumoniae, whereby capsule formation interfered at the transcriptional level with the adhesin biosynthesis [12]. It is possible that in some cases, represented by a small fraction of the cell population of the K21a/s variant, ¢mbrial assembly is altered by another mechanism because the variant exhibited traces of FimH antigen activity in the PP space only.…”
Section: Impairment Of ¢Mbrial Subunit Assembly In Encapsulated K Pnsupporting
confidence: 61%
See 1 more Smart Citation
“…Expression of capsule in some way interferes with one of the ¢nal stages of ¢mbrial assembly. A similar inverse relationship has recently been described for CF29K adhesin of K. pneumoniae, whereby capsule formation interfered at the transcriptional level with the adhesin biosynthesis [12]. It is possible that in some cases, represented by a small fraction of the cell population of the K21a/s variant, ¢mbrial assembly is altered by another mechanism because the variant exhibited traces of FimH antigen activity in the PP space only.…”
Section: Impairment Of ¢Mbrial Subunit Assembly In Encapsulated K Pnsupporting
confidence: 61%
“…The knowledge on the regulation of capsule formation is rather limited. It involves the products of rmpA and RcsA genes which also regulate the synthesis of polysaccharides in enterobacteria [10,11] and recently was reported to be in£uenced by environmental conditions [12]. In the present study, we sought to determine the relationship between the phenotypic expression of capsular material and type 1 ¢mbriae in K. pneumoniae.…”
Section: Introductionmentioning
confidence: 95%
“…In this regard, their inhibitory effect can be compared with that of negatively charged surface sialic acids. Although on rare occasions, capsules are themselves involved in adhesion, in general, capsules inhibit OMP function in a wider setting and can be demonstrated in a range of capsule types and OMP adhesin types extending to distinct species (St Geme and Cutter, 1996;Favre-Bonte et al, 1999;Cywes and Wessels, 2001;Joseph and Wright, 2004). It is therefore likely in general that, when capsule is itself not an adhesin, the basis of its inhibitory action may reside in physical masking and/ or its physicochemical properties which may neutralize the charge of an adhesin.…”
Section: Cho-cc1lomentioning
confidence: 99%
“…Only one study has investigated the role of capsule in K. pneumoniae UTI with inconclusive results [11] and studies on the role of capsule in GI colonization are contradictory [12,13]. Interestingly, recent studies have shown that expression of capsule impedes the ability of K. pneumoniae to adhere to and invade epithelial cells in vitro [14,15]. These studies suggest that expression of capsule may be a disadvantage in serum poor host compartments by reducing the ability of the bacteria to adhere to epithelial surfaces.…”
Section: Introductionmentioning
confidence: 99%
“…Only the K2-serotype gene cluster has been cloned and the genomic organization determined [9,16]. However, only a few open reading frames have been assigned a function and only some parts of the cluster are conserved among di¡erent capsule serotypes [14,16]. Due to the inability to construct well-de¢ned isogenic mutants, most studies investigating the role of capsule on the virulence of K. pneumoniae are based on the use of non-capsulated variants (NCVs) arisen either spontaneously or after mutagenic treatment of the bacteria.…”
Section: Introductionmentioning
confidence: 99%